One-Step Cannulation and Distance Measurement during Aortic Branched Endograft Repair: The Neuron Catheter Trick - Gioele Simonte; Gianluigi Fino; Gianbattista Parlani; Rachele Simonte; Giacomo Isernia (Medical Sciences)
Purpose: This paper aims to describe a straightforward, efficient, and reliable technique to simplify cannulation maneuvers during aortic branched endograft repair. Technique: The suggested approach utilizes the Penumbra Neuron Select catheter, which combines diagnostic, sizing, and support capabilities in one. This has the potential to reduce procedural time and minimize the need for serial catheter and guidewire exchanges. Conclusions: The proposed technique offers a simple yet effective tool to mitigate the risk of vessel loss and injury, and to streamline complex aortic repair procedures.